Estimating the real contact area in lubricated hot rolling of aluminium. (February 2023) - Rudnytskyj, André; Vorlaufer, Georg; Leimhofer, Josef; Jech, Martin; Gachot, Carsten
Abstract: Predictions of the real contact area in metal forming processes are essential for the calculation of friction and, consequently, the optimisation of energy consumption and quality of rolled products. This study develops of a model for estimating the real contact area in hot rolling of a 6061 aluminium alloy based on: thermo-viscoplastic material properties, measured roll topography, and hydrodynamic and hydrostatic roles of lubricant in the contact. Results show the interplay between load and contact area, as regions of solid contact, fluid channels and pockets are formed. Quantification in a rolling pass shows both solid contact and lubricant entrapment play the major roles, which is highly determined by the topography and the flow stress of the workpiece. Graphical abstract: Highlights: Topography measurement of roll used in hot rolling of aluminium. Inclusion of thermo-viscoplasticity, topography and lubricant in contact model. Quantification of solid, channels and pockets regions in contact load and area. Application and evaluation of methodology in rolling pass.